2006
DOI: 10.1096/fj.06-6250fje
|View full text |Cite
|
Sign up to set email alerts
|

Docosahexaenoic acid (DHA) blunts liver injury by conversion to protective lipid mediators: protectin D1 and 17S‐hydroxy‐DHA

Abstract: Docosahexaenoic acid (DHA) is a omega-3 essential fatty acid that reduces the incidence and severity of a number of diseases. Recently, a novel series of DHA-derived lipid mediators with potent protective actions has been identified. In this study we demonstrate that dietary amplification of these DHA-derived products protects the liver from necroinflammatory injury. In vitro, supplementation of hepatocytes with DHA significantly reduced hydrogen peroxide-induced DNA damage, evaluated by the "comet assay," and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
144
1
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 198 publications
(162 citation statements)
references
References 50 publications
11
144
1
3
Order By: Relevance
“…Metabolic syndrome is linked to inflammatory changes in both WAT and liver [1]. In this study, in accordance with the previous findings [17,18,21], dietary LC n-3 PUFA supplementation resulted in the inhibition of formation of various LC n-6 PUFA-derived pro-inflammatory eicosanoids in both tissues as well as in the induction of the antiinflammatory molecules. In WAT, in contrast to the liver, the levels of EPA, DHA, AA and their active metabolites, including the anti-inflammatory molecules PD1 and prostaglandin 15d-PGJ 2, were increased in a synergistic manner by the combination treatment (Fig.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Metabolic syndrome is linked to inflammatory changes in both WAT and liver [1]. In this study, in accordance with the previous findings [17,18,21], dietary LC n-3 PUFA supplementation resulted in the inhibition of formation of various LC n-6 PUFA-derived pro-inflammatory eicosanoids in both tissues as well as in the induction of the antiinflammatory molecules. In WAT, in contrast to the liver, the levels of EPA, DHA, AA and their active metabolites, including the anti-inflammatory molecules PD1 and prostaglandin 15d-PGJ 2, were increased in a synergistic manner by the combination treatment (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…They can act as ligands for surface receptors or can interact with signalling proteins including the transcription factors peroxisome proliferator-activated receptor γ (PPARγ) and nuclear factor κ light-chain enhancer of activated B cells (NF-κB) [19]. Notably, resolvins and protectins mediate the antiinflammatory and protective actions of LC n-3 PUFA in obesity-induced insulin resistance and hepatic steatosis [17,21]. As LC n-3 PUFA and LC n-6 PUFA compete for common enzymatic pathways, a relatively small increase in the LC n-3 PUFA intake usually slows down synthesis of pro-inflammatory metabolites derived from arachidonic acid (AA; 20:4 n-6) [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, these n-3 PUFA-derived lipid mediators showed potent protective actions in an experimental brain ischemic reperfusion model and in obesity-induced insulin resistance and steatosis [22][23][24][25][26] . Of particular interest is resolvin E1, a representative member of these novel lipid autacoids.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, hepatocytes from transgenic fat-1 mice, which have increased levels of resolvins, and wild-type hepatocytes incubated with nanomolar concentrations of RvD1, show a reduction in neutral lipid accumulation (steatosis) as well as inflammation (Lopez-Vicario et al, 2015b, 2014. In addition, PD1 and 17S-HDHA are able to attenuate DNA damage and oxidative stress in hepatocytes and reduce TNFa release in macrophages (Gonzalez-Periz et al, 2006), whereas LXA 4 and AT-LXA 4 efficiently block IL-8 secretion by hepatocytes (Planaguma et al, 2002). Moreover, in precision-cut liver slices, an ex vivo model that overrides the influence of extrahepatic circulating factors, Rius and collaborators have demonstrated that RvD1 reduces hypoxia-induced mRNA and protein expression for inflammatory genes including COX-2, IL1b, IL-6 and CCR7 .…”
Section: Biological Actions Of Omega-3-derived Lipid Mediators In Watmentioning
confidence: 99%